Answer:
Step-by-step explanation:
Given
Required
Determine
In functions;
So, we have:
Substitute values for R(x) and C(x)
Open bracket
Collect Like Terms
X^-6
You can find the derivative:
-6x^ -7
The ratio is 34:60
Gotta add 39 and 31, then subtract 26.
Answer:
<em>x = 4 / 3, y = 7 / 3</em>
Step-by-step explanation:
We are given the following system of equations;
{ 7x - y = 7, ⇒ Let us multiply the first equation by 2,
x + 2y = 6 }
2 * ( 7x - y = 7 ) ⇒ 14x - 2y = 14 ⇒ Now add the two equations
+ x + 2y = 6 + x + 2y = 6
14x + x = 14 + 6 ⇒ Simplify
15x = 20,
<em>x = 4 / 3</em> ⇒ Now substitute this value of x into the first equation to solve for the value of y,
7 * ( 4 / 3 ) - y = 7 ⇒ Simplify,
28 / 3 - y = 7,
y = 7 / 3
<em>Solution; x = 4 / 3, y = 7 / 3</em>
Answer:
Step-by-step explanation:
(6.8 x 10^-8) + (1.7 x 10^-6)
(0.068 x 10^-6) + (1.7 X 10^-6)
(0.068 + 1.7) x 10^-6
= 1.768 x 10^-6
First you have to convert the (6.8 x 10^-8) to be compatible with 10^-6 so you would move the decimal place 2 places to the right since -8 and -6 are 2 digits apart. Think of it like fractions, to add them they must have the same denominator.
Then once you have converted the 6.8 to 0.068 you can add it to the 1.7.
And now you have your final answer, 1.768 x 10^-6.